Compact X/Ka-Band Dual-Polarization Spaceborne Digital Beamforming Synthetic Aperture Radar - Patyuchenko, Anton; Younis, Marwan; Krieger, Gerhard (International Radar Symposium (IRS), 2015)
This paper presents a spaceborne Synthetic Aperture Radar (SAR) system based on a highly-integrated digital beamforming (DBF) X/Ka-band receiver platform with a dual-polarization capability. Compact modular architecture of the proposed system enables the realization of various configurations of spaceborne SAR missions. This paper describes the proposed radar concept and presents one of the potential missions considering its operational scenario, instrument parameters and resulting performance characteristics.
DLR Import::2019-04-03